Broad-spectrum in vitro activity of macrophage infectivity potentiator inhibitors against Gram-negative bacteria and Leishmania major. (4th March 2022) - Iwasaki, Jua; Lorimer, Donald D.; Vivoli-Vega, Mirella; Kibble, Emily A.; Peacock, Christopher S.; Abendroth, Jan; Mayclin, Stephen J.; Dranow, David M.; Pierce, Phillip G.; Fox, David; Lewis, Maria; Bzdyl, Nicole M.; et al.
Abstract: Background: The macrophage infectivity potentiator (Mip) protein, which belongs to the immunophilin superfamily, is a peptidyl-prolyl cis / trans isomerase (PPIase) enzyme. Mip has been shown to be important for virulence in a wide range of pathogenic microorganisms. It has previously been demonstrated that small-molecule compounds designed to target Mip from the Gram-negative bacterium Burkholderia pseudomallei bind at the site of enzymatic activity of the protein, inhibiting the in vitro activity of Mip. Objectives: In this study, co-crystallography experiments with recombinant B. pseudomallei Mip (BpMip) protein and Mip inhibitors, biochemical analysis and computational modelling were used to predict the efficacy of lead compounds for broad-spectrum activity against other pathogens. Methods: Binding activity of three lead compounds targeting BpMip was verified using surface plasmon resonance spectroscopy. The determination of crystal structures of BpMip in complex with these compounds, together with molecular modelling and in vitro assays, was used to determine whether the compounds have broad-spectrum antimicrobial activity against pathogens. Results: Of the three lead small-molecule compounds, two were effective in inhibiting the PPIase activity of Mip proteins from Neisseria meningitidis, Klebsiella pneumoniae and Leishmania major. The compounds also reduced the intracellular burden of these pathogens using in vitro cell infection assays. Conclusions: These results indicate that Mip is a novel antivirulence target that can be inhibited using small-molecule compounds that prove to be promising broad-spectrum drug candidates in vitro . Further optimization of compounds is required for in vivo evaluation and future clinical applications.